Effect Of Cutting Length On Vanilla Plant Roots (Vanilla planifolia Andrew) - Anita_Cristi Lempoy; Jemmy Najoan; James B. Kaligis (Jurnal Agroekoteknologi Terapan, 2023)
This research was carried out in Sea II Village, Pineleng District,Minahasa Regency in August-September 2022. This study aims to determine the best cutting length for the growth of vanilla plant roots (Vanilla planifolia Andrew). This study used a randomized blok design (RAK) consisting of 6 treatments and 3 replications for each treatment totaling 4 plants so that the number of plants was 72 plants. The observed variable measured are the time of emergence of roots, percentage of long roots, roots, number of roots and root dry weight. The results showed that the length treatment of cutting B6 (12 standard ) resultted in the fastest emergenci time, the longest roots length, the highest number of roots and the largest dry weight compared to other treatments. Keywords: Cuttings, Rooting, Vanilla planifolia Andrew Abstrak Penelitian ini di laksanakan di desa Sea II, Kecamatan Pineleng, Kabupaten Minahasa pada bulan Agustus-September 2022. Penelitian ini bertujuan untuk mengetahui Panjang Stek terbaik Untuk Pertumbuhan akar tanaman vanili (Vanilla planifolia Andrew). Penelitian ini menggunakan Rancangan Acak kelompok (RAK) yang terdiri dari 6 perlakuan dan 3 ulangan setiap perlakuan berjumlah 4 tanaman sehingga jumlah tanaman sebanyak 72 tanaman. Variabel pengamatan yang diukur adalah waktu muncul akar, persentase berakar , panjang akar, jumlah akar dan bobot kering akar. Hasil penelitian menunjukkan bahwa perlakuan panjang stek B6 (12 buku) menghasilkan waktu muncul akar tercepat, panjang akar terpanjang,jumlah akar terbanyak dan bobot kering terbesar.   Kata Kunci :Stek, Perakaran, Vanilla planifolia Andrew